Leptomeningeal Dissemination in Choroid Plexus Tumors: Magnetic Resonance Imaging Appearance and Risk Factors - Daniel Nunes do Espirito Santo; Monika Warmuth-Metz; Camelia-Maria Monoranu; Martin Hasselblatt; Christian Thomas; Torsten Pietsch; Jürgen Krauß; Tilmann Schweitzer; Brigitte Bison; Matthias Eyrich; Uwe Kordes; Denise Obrecht-Sturm; et al. (Children)
Background: Intracranial choroid plexus tumors (CPT) are rare and primarily affect young children. Leptomeningeal dissemination (LMD) has been reported not only in high-grade choroid plexus carcinoma (CPC) but also in lower histological grades; however, a systematic evaluation of CPT-specific imaging characteristics remains lacking. Methods: We analyzed the imaging characteristics of LMD in a single-center pediatric cohort of 22 CPT patients (thirteen choroid plexus papilloma (CPP), six atypical choroid plexus papilloma (aCPP), three CPC), comparing LMD features with those of the primary tumor. Additionally, we examined the correlation between resection status and LMD development during follow-up. Results: At diagnosis, we observed true LMD in three (two CPCs, one CPP) and pseudo-LMD in one case (CPP). During follow-up, two CPP patients developed cystic LMD, and one aCPP patient developed a solid metastasis. LMD had characteristics of the primary tumor in 3/4 cases. Incomplete resection was associated with a higher risk of LMD (p = 0.025). Conclusions: LMD can occur in both high- and lower-grade CPT, presenting at diagnosis as well as in relapsed lower-grade cases. Notable MR-imaging features include pseudo-LMD at diagnosis and cystic LMD in relapsed CPP cases. Incomplete tumor resection may increase the risk of LMD, although further validation is needed.